Arteriovenous Malformation of Upper Lip - a short cure for gross deformity - Sundas Javeed, Farid Ahmad Khan, Muhammad Awais, Rizwan Khan, Rooh-Ul-Ain, Ayesha Waheed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the safety and success of facial artery ligation alone in arteriovenous malformation of upper lip in non-affording patients. Methodology: This prospective study was conducted at Department of Plastic surgery, on 11 consecutive patients with recurrent upper lip arteriovenous malformation who couldn’t afford angioembolization and frequent hospital visits for staged procedures. We did debulking of lesion after facial artery ligation and cosmetic lip correction. Results: Total 11 patients (9 males and 2 females) were included in this study. Majority of patients showed satisfactory results with facial artery ligation alone. One patient lost the follow up. No significant complication was noted in any patient. No recurrence was noted at 6 months and 1 year follow-up. Patient satisfaction rate remained 8.6±0.96 as per VAC. Conclusion: facial artery ligation alone provides an easy and approachable option for arteriovenous malformation where cost affordability for angioemboization and repeated hospital visits are main limitations.